Pancreatic Cystic Lesions: Pathogenesis and Malignant Potential - Pusateri, Antoinette J. (Diseases, 2018)
Pancreatic cancer remains one of the most lethal cancers despite extensive research. Further understanding of precursor lesions may enhance the ability to treat and prevent pancreatic cancer. Pancreatic cystic lesions (PCLs) with malignant potential include: mucinous PCLs (intraductal papillary mucinous neoplasms and mucinous cystic neoplasm), solid pseudopapillary tumors and cystic neuroendocrine tumors. This review summarizes the latest literature describing what is known about the pathogenesis and malignant potential of these PCLs, including unique epidemiological, radiological, histological, genetic and molecular characteristics.